The use of virtual reality technology in the studying of physics - Daineko, Ye.A.; Ipalakova, M.T.; Tsoy, D.D.; Baurzhan, Zh.B.; Yelgondy, Ye.K.; Bolatov, Zh.Zh. (Recent Contributions to Physics, 2019)
With the development of information technology, other industries are also developing, completely new and unfamiliar ways of communication, creation, and learning are becoming popular. Thus, the modern world makes new demands on the learning process. However, despite the development of distance and inclusive education, the natural sciences due to their peculiarities lag behind other fields of science. This is due to the fact that in order to effectively acquire skills in working with equipment and the ability to analyze experimental data, physics, chemistry, and other exact sciences require executing laboratory works. However, this requires specially equipped laboratories that are not always staffed in educational institutions. Then, new technologies, such as computer graphics, augmented reality, computational dynamics and others come to the rescue. This article discusses the use of modern technologies in the field of education. The analysis of the introduction of various innovative developments with the virtual reality into some spheres of modern life was also conducted. The work introduces the advantages and possibilities of using educational resources based on the virtual reality in education and, in particular, for studying physics. The authors present the software that allows studying physics with the help of virtual reality. Such approach made the interaction with the application more interesting and memorable, and learning more effective. As development platform the cross platform Unity 3D environment was chosen. The main functionality was written in C#. Graphic models were created using Substance Painter. Additionally, in the article the development process of the application was considered along with its functionality and user interface. The work done allowed the authors to identify the advantages of using new technologies in the study of physics and showed that they open new prospects for their wide application at different stages of education in educational institutions of various levels. This approach in addition to the advantages mentioned above makes the learning process safe, interesting and more accessible. As a result, not only software was developed, but new experience was gained, which will be used for further development and research.